ANALISA PEMANFAATAN BRIKET LIMBAH ARANG KAYU ALABAN DI DESA TAPUK KECAMATAN LIMPASU KABUPATEN HULU SUNGAI TENGAH - Muhammad Nizar Ramadhan; Andy Nugraha (Universitas Lambung Mangkurat, 2020)
The solution to reduce the use of fossil fuels is by utilizing renewable energy such as solar power, wind power, and hydropower, as well as the utilization of other alternative energy derived from biomass. One of alternative energy from biomass that is very potential is briquettes. Tapuk Village, Limpasu Subdistrict, Hulu Sungai Tengah Regency is one of the producers of Alaban wood charcoal, with grade D charcoal in the form of charcoal flakes and is often regarded as waste. This study aims to determine the physical properties of alaban wood charcoal waste briquettes which include water content, ash content, volatile matter content, fixed carbon content, and calorific value, as well as the potential utilization of alaban wood charcoal waste briquettes. so that residents can use Tapuk Village, Limpasu District, Hulu Sungai Tengah Regency as an alternative fuel to substitute kerosene and LPG. The results showed the physical properties of alaban wood charcoal waste briquettes for 3.66 % water content, 3.15 % ash content, 14.31 % volatile matter content, 78.88% fixed carbon content, 6.259.33 cal / gr calorific value. The use of alaban wood charcoal waste briquettes is able to produce consumption costs efficiency of 60% better than the use of LPG and 70% better than the use of kerosene.